Cognitive impairment associated with Hodgkin's lymphoma and chemotherapy - Fayette, Dan; Juríčková, Veronika; Kozák, Tomáš; Mociková, Heidi; Gaherová, Lubica; Fajnerová, Iveta; Horáček, Jiří (Neuroscience letters, 2023)
Chemotherapy-related cognitive impairment (CRCI) is a well-documented side effect of cancer treatment in various types of tumors including Hodgkin's lymphoma (HL). However, a longitudinal study evaluating the cognitive performance of HL patients has been completely lacking. The aim of the study was to determine the presence of CRCI in HL patients before, promptly after, and 6 months after treatment. Thirty-six patients newly diagnosed with HL and 45 healthy controls (HC) completed the neuropsychological battery and psychological measures of affective distress and quality of life. The results indicate that HL patients have impaired performance compared to HC which cannot be explained by emotional factors. Cognitive impairments prior to treatment were found in 3 of 6 cognitive domains, i.e., verbal memory and learning, speed of processing/psychomotor speed, and abstraction/executive function. Promptly after the chemotherapy, deficits were found in the domains of memory and learning, verbal memory, speed of processing/psychomotor speed, and abstraction/executive function. Weaker cognitive performance persist even 6 months after the end of chemotherapy, specifically in domains of verbal memory and learning, and abstraction/executive function. Our results indicate the presence of cognitive impairment in HL patients already prior to treatment and increased damages caused by chemotherapy, while some of them may last for up to 6 months after the treatment.
Keywords: longitudinální studie; Cognitive Dysfunction; exekutivní funkce; lidé; Chemotherapy; Hodgkin’s lymphoma; Chemotherapy-related cognitive deficit; Hodgkin Disease; kvalita života; neuropsychologické testy; Humans; Neuropsychology; kognitivní dysfunkce; Executive Function; Hodgkinova nemoc; Longitudinal Studies; Quality of Life; Neuropsychological Tests; Cancer